Scientific Literacy Profile in The Maritime Context of Senior High School Students in Dumai - Ranty, Devia; Ma’aruf, Zuhdi (Journal of Indonesian Science Teachers, 2023)
Scientific literacy is a part of 21st-century skills that must have by students in order to use their knowledge properly. This research is motivated by the current state of education which is intensively developing scientific literacy skills in the school. This is caused by science and technology development, so students are required to be able to adapt to technology, science, environment, and society. This research aimed to reveal MAN 1 Dumai students’ ability based on scientific literacy in the maritime context. The survey method used in this study with 164 samples. The scientific literacy of the students was measured by using a scientific literacy test referring to the PISA 2015 scientific literacy competence aspects. The results of descriptive analysis show that the scientific literacy of MAN 1 Dumai student’s is in the sufficient category with an average score 60.27. Scientific literacy in the competence to explain scientific phenomena is in the sufficient category with an average 61.51, while in evaluating and designing scientific inquiry is in the sufficient category with an average 56.95. Meanwhile, interpreting data and evidence scientifically is in the sufficient category with an average 60.71. Then based on the inferential test, there is no significant difference between male and female students about the level of scientific literacy